The Role of Husband and Family Support in Reducing Baby Blues Symptoms in Postpartum Mothers - Yenni Kristiana (Oshada, 2025)
The postpartum period is a challenging transition period, with significant physical, psychological, and social changes for mothers. One common condition is baby blues, a mild mood disorder that usually appears in the first two weeks after giving birth. Around 70-80% of mothers experience baby blues symptoms such as anxiety, fatigue, and difficulty sleeping, which can disrupt the early relationship between mother and baby and slow recovery. Despite its high prevalence, this disorder is often considered normal and does not require intervention, whereas if not handled properly, the symptoms can develop into postpartum depression. Research shows that adequate emotional support from husbands and families can significantly reduce these symptoms. Unfortunately, many families lack understanding of postpartum psychological conditions, so they often provide unsupportive responses, which actually worsen the mother's condition. This study uses a descriptive qualitative approach to describe the experiences of mothers facing baby blues and the role of husband and family support in their recovery. The findings of this study emphasize the importance of education about postpartum maternal mental health and the need for changes in the social support system to be more sensitive and responsive to reduce the psychological impact on mothers and children